Customer experience and satisfaction in coffee consumption: an experiential marketing perspective - Supawat Meeprom; Akkhaporn Kokkhangplu (Cogent Business & Management)
The purpose of this study was to explore structural relationships among customer experience, customer satisfaction, advocacy and repurchase intentions—with emphasis on the mediating effect of tourist satisfaction on relations (1) between customer experience and customer advocacy and (2) between customer experience and repurchase intentions—in the context of speciality coffee cafés in Thailand. Purposive sampling via a self-administered survey approach was employed. Data from 300 valid questionnaires were included in a path analysis using partial least squares structural equation modelling (PLS-SEM). Drawing on social exchange theory, the results of the study indicated that customer satisfaction was influenced positively and directly by affective, sensorial and intellectual experiences. Customer advocacy was positively and directly influenced by intellectual experience, and repurchase intentions was positively and directly influenced by sensorial and intellectual experiences. The results also indicated the existence of an indirect relationship of sensory, affective and intellectual experiences with customer advocacy and that repurchase intentions had a mediating effect on customer satisfaction. The results of this research offer a deeper understanding for speciality coffee café managers in creating specific experiences of customer perception and in building effective marketing strategies for speciality coffee at a café.